Switching colours: Becoming a culturally responsive teacher educator - Campbell, B. (South African Journal of Higher Education, 2018)
This narrative inquiry self-study project explores ways to bridge the socio-cultural and cognitive gap between myself, my pre-service teacher education students and the characters and events in a Victorian novel. In the study I investigate the students’ cultural capital through focus groups, conversations and classroom activities. A self-reflective journal relates how I translated what I learned about the students’ beliefs, attitudes and experiences into teaching that was culturally responsive, purposeful and underpinned by constructivism. My findings were that in getting to know the students, I was able to respond to their contexts and construct knowledge jointly through purposeful pedagogy. In doing so, the chasm between myself, the students and the novel narrowed.